Field‐assisted paper spray mass spectrometry for therapeutic drug monitoring: 1. the case of imatinib in plasma. (8th May 2017) - D'Aronco, S.; Dall'Armi, M.; Crotti, S.; Calandra, E.; Traldi, P.; Di Marco, V.; Buonadonna, A.; Corona, G.; Giodini, L.; Marangon, E.; Posocco, B.; Toffoli, G.; et al.
Abstract : The field‐assisted paper spray (FAPS) – mass spectrometric method has been employed to quantify the imatinib (IMT) plasma levels in treated patients. The quantitative measurements have been performed on the collisionally generated fragment at m/z 394 of the protonated molecules of IMT and deuterated IMT ( d 3 ‐IMT), used as internal standard. The FAPS‐tandem mass spectrometry (MS/MS) method exhibits some limitations, because of the high number of operative parameters that need to be carefully controlled. For this aim, papers of different geometry, thickness, and porosity were tested. To obtain a more focalized and intense electrical field, a stainless steel needle was mounted axially and placed at 4 kV voltage. The variability observed in the measurements was ascribed either to the inter‐individual variability (e.g. the concomitant presence of other compounds such as proteins, lipids, drugs and/or salts in the plasma of different patients) or to the uncontrollable variables in the instrumental set‐up (e.g. sample deposition, changes in paper spray conditions). Furthermore, the manual sample deposition and solvent dripping strongly affects the measure reproducibility. Despite this, it is interesting to observe that, once applied in blind on 24 real plasma samples, FAPS‐MS/MS led to results analogous to those obtained by the well‐consolidated liquid chromatography‐MS/MS, even if the mean coefficient of variation % (CV%) values of 20.4% and 2.6% were observed for the two methods, respectively. In conclusion, despite CV values are relatively high, it is worth noting that the FAPS‐MS/MS method is much more straightforward, rapid and economical than the liquid chromatography‐MS/MS one, and it appears therefore very promising for applications where a high precision is not always a required task, as e.g. in some cases of therapeutic drug monitoring. Copyright © 2017 John Wiley & Sons, Ltd.